Familiarization, validity and smallest detectable difference of the isometric squat test in evaluating maximal strength. Issue 18 (17th September 2018) - Drake, David; Kennedy, Rodney; Wallace, Eric
ABSTRACT: Isometric multi-joint tests are considered reliable and have strong relationships with 1RM performance. However, limited evidence is available for the isometric squat in terms of effects of familiarization and reliability. This study aimed to assess, the effect of familiarization, stability reliability, determine the smallest detectible difference, and the correlation of the isometric squat test with 1RM squat performance. Thirty-six strength-trained participants volunteered to take part in this study. Following three familiarization sessions, test–retest reliability was evaluated with a 48-hour window between each time point. Isometric squat peak, net and relative force were assessed. Results showed three familiarizations were required, isometric squat had a high level of stability reliability and smallest detectible difference of 11% for peak and relative force. Isometric strength at a knee angle of ninety degrees had a strong significant relationship with 1RM squat performance. In conclusion, the isometric squat is a valid test to assess multi-joint strength and can discriminate between strong and weak 1RM squat performance. Changes greater than 11% in peak and relative isometric squat performance should be considered as meaningful in participants who are familiar with the test.